Questioning Breath: A Digital Dive into CO2 Levels - Silvia Casalinuovo; Alessio Buzzin; Antonio Mastrandrea; Marcello Barbirotta; Donatella Puglisi; Giampiero de Cesare; Domenico Caputo (Proceedings)
This work presents a smart mask for real-time monitoring of carbon dioxide (CO2) levels as a reference tool for diagnosis, sports training and mental health status. A printed circuit board was projected and fabricated to gain data with real-time visualization and storage on a database, enabling remote monitoring as a needed skill for telemedicine purposes. The electronics were inserted in a wearable device—shaped like a mask—and 3D-printed with biocompatible materials. The whole device was used for analyzing CO2 on a breath volunteer in three kinds of measurement.